1969
DOI: 10.1002/pol.1969.160070306
|View full text |Cite
|
Sign up to set email alerts
|

Structure of poly(N‐butyl isocyanate)

Abstract: An x‐ray study of poly(N‐butyl isocyanate) (PBIC) was undertaken with the aim of providing the structural information required for the calculation of its ultraviolet absorption spectrum. Well defined diffraction patterns are obtained from powder samples and oriented films of the polymer cast from cyclohexane solution. All the reflections can be satisfactorily indexed in terms of a pseudo‐hexagonal unit cell with a = 13.3 Å and c = 15.4 Å. This indexing and the intensity distribution lead to the conclusion that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
69
0
1

Year Published

1999
1999
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(72 citation statements)
references
References 13 publications
2
69
0
1
Order By: Relevance
“…This speculation is supported by the fact that st-PMMA can encapsulate fullerenes and it-PMMA within its helical cavity to form robust and peapod-like inclusion complexes 80 and a stereocomplex, 98 respectively. Recently, we found that a preferred-handed helical st-PMMA can be induced in toluene in the presence of optically active alcohols, such as (S)-or (R)-2-phenylethanol (38), resulting in an optically active gel, which showed a VCD in PMMA infrared regions. On addition of fullerenes, such as C 60 , helical st-PMMA traps fullerenes within its helical cavity to form an optically active peapod-like inclusion complex ( Figure 14).…”
Section: Synthesis and Structures Of Helical Polymers E Yashimamentioning
confidence: 99%
See 2 more Smart Citations
“…This speculation is supported by the fact that st-PMMA can encapsulate fullerenes and it-PMMA within its helical cavity to form robust and peapod-like inclusion complexes 80 and a stereocomplex, 98 respectively. Recently, we found that a preferred-handed helical st-PMMA can be induced in toluene in the presence of optically active alcohols, such as (S)-or (R)-2-phenylethanol (38), resulting in an optically active gel, which showed a VCD in PMMA infrared regions. On addition of fullerenes, such as C 60 , helical st-PMMA traps fullerenes within its helical cavity to form an optically active peapod-like inclusion complex ( Figure 14).…”
Section: Synthesis and Structures Of Helical Polymers E Yashimamentioning
confidence: 99%
“…47 This helical structure is comparable in structure with the corresponding helical polyisocyanate proposed by the fiber XRD method. 38 The single-X-ray crystallographic analysis of uniform oligomers has also been used to determine the helical structures of poly(2,3-quinoxaline)s 48 and N-substituted poly(p-benzamide)s, 49 which are considered to possess a one-handed helical conformation as evidenced by their intense Cotton effects. An optically and catalytic active pentamer of a diastereomerically pure oligo(2,3-quinoxaline) (16) was found to have a right-handed 5/2 helix in the solid state.…”
Section: Helical Structure Determination By Single-crystal X-ray Analmentioning
confidence: 99%
See 1 more Smart Citation
“…The obtained PHIC product was characterized using both proton and carbon nuclear magnetic resonance ( 1 H and 13 C NMR) spectroscopies with a JEOL NMR spectrometer (model JNM-LA300WB, JEOL Ltd, Tokyo, Japan) and using Fourier transform infrared (FT-IR) spectroscopy with a Perkin Elmer spectrometer (model 2000, Perkin Elmer, Waltham, MA, USA Figure S1). 13 The molecular weights of the polymers were determined using a multi-angle laser light scattering detector system and a size exclusion chromatography system (Interferometric Refractometry 478-009-690, Optilab DSP, Phoeix, AZ, USA and DAWN EOS Laser Photometer 113-E, Wyatt Technology, Santa Barbara, CA, USA) with four columns (HR 0.5, HR 1, HR 3 and HR 4, Waters Styragel columns run in series with column pore sizes of 50, 100, 500 and 1000 Å , respectively). THF with triethylamine (to prevent the adsorption of the hydrophilic polymer on the column) was used as the mobile phase at a flow rate of 1.0 ml per min.…”
Section: Materials and Phic Synthesismentioning
confidence: 99%
“…For example, several helical conformations have been proposed, namely 2 1 , 5 1 and 8 3 in solution [9][10][11][12] and 8 3 , 8 5 and 12 5 in the solid state. [13][14][15] Furthermore, triclinic, monoclinic and pseudo-hexagonal lattices have all been proposed as possible molecular packing structures. 13,14,16 In the present work, we provide the first report on the formation of PHIC in thin films with both a helical conformation-based hexagonal packing order and a b-sheet conformation-based lamellar structure;…”
Section: Introductionmentioning
confidence: 99%